2019
DOI: 10.1111/1747-0080.12579
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nutritional status, muscle mass and oral status on recovery of full oral intake among stroke patients receiving enteral nutrition: A retrospective cohort study

Abstract: Aim: To clarify the correlation between malnutrition, muscle mass and oral status, and swallowing function recovery in stroke patients receiving enteral nutrition. Methods: Patients with stroke and dysphagia receiving any amount of enteral nutrition in rehabilitation wards from 2012 to 2016 were eligible for inclusion in this retrospective study. On admission, body composition by bioimpedance analysis, malnutrition confirmed by the European Society for Clinical Nutrition and Metabolism criteria, oral status, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Hence, even in acute care settings, proper dysphagia rehabilitation must be started at an early stage after stabilisation of the patient's general condition 9 . Improvement of the oral status and function is important to conduct dysphagia rehabilitation safely 10 . However, inpatients with dysphagia, particularly elderly patients, have poor oral health and hygiene with a high prevalence of caries, periodontal disease and edentulous jaws 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, even in acute care settings, proper dysphagia rehabilitation must be started at an early stage after stabilisation of the patient's general condition 9 . Improvement of the oral status and function is important to conduct dysphagia rehabilitation safely 10 . However, inpatients with dysphagia, particularly elderly patients, have poor oral health and hygiene with a high prevalence of caries, periodontal disease and edentulous jaws 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sarcopenia can be developed in cerebrovascular patients regardless of swallowing ability. As previous studies showed a relationship between decreased muscle mass, the onset of dysphagia and poor recovery of swallowing function [44,45], the association between dysphagia and sarcopenia would be strengthened in patients without cerebrovascular disease.…”
Section: Potentially Associated Factors Of the Co-msmentioning
confidence: 91%
“…The risk of malnutrition in patients without dysphagia increases if long-term energy intake insufficiency is accompanied by insufficient protein intake, suggesting that monitoring nutritional intake is necessary. The loss of consciousness (29,30), poor oral hygiene (31), depression (32), reduced mobility (30), and limb and face weakness are associated with a high risk of malnutrition. During hospitalization, age, IS, National Institutes of Health Stroke Scale (NIHSS) score at admission, geriatric nutritional risk index (GNRI) at admission (33).…”
Section: Risk Factors Of Malnutrition In Stroke Patientsmentioning
confidence: 99%